A common antigenic determinant of vimentin and desmin defined by monoclonal antibody - Dráberová, E; Dráber, P; Havlícek, F; Viklický, V (Folia biologica, 1986)
A monoclonal antibody, VI-01, to vimentin and desmin has been isolated from a fusion of mouse myeloma cells with immune spleen cells. The antibody appeared specific for vimentin of various species and smooth muscle desmin and did not recognize other intermediate filament proteins when cell lines and tissue sections were assayed in immunofluorescence and cell lysates in immunoblotting. The binding test with purified vimentin and desmin confirmed these results. The antibody can differentiate carcinomas from sarcomas in human diagnostic surgical pathology.
Keywords: Cell Line; Rats; křečci praví; monoklonální protilátky; Antibodies, Monoclonal; Mice; desmin; Desmin; krysa rodu Rattus; Muscle, Smooth; zvířata; Humans; vimentin; Species Specificity; myši; Cricetinae; buněčné linie; druhová specificita; Vimentin; Epitopes; hladké svalstvo; lidé; epitopy; Animals